Biology: Macmillan Science Library - Robinson, Richard (Macmillan Reference USA, 2011)
In addition to explaining biological concepts, Biology reviews the history of science, explores related fields, discusses critical issues such as embryogenesis and commercial applications of research in biology and addresses ethical issues. Careers in biology are also explored. Each fully illustrated volume contains sidebars, bibliographies, timelines, charts, a glossary and individual and cumulative indexes.